Occurrence of Anticyclonic Tornadoes in a Topographically Complex Region of Mexico - Noel Carbajal; José F. León-Cruz; Luis F. Pineda-Martínez; José Tuxpan-Vargas; Juan H. Gaviño-Rodríguez (Advances in Meteorology)
Tornadoes are violent and destructive natural phenomena that occur on a local scale in most regions around the world. Severe storms occasionally lead to the formation of mesocyclones, whose direction or sense of rotation is often determined by the Coriolis force, among other factors. In the Northern Hemisphere, more than 99% of all tornadoes rotate anticlockwise. The present research shows that, in topographically complex regions, tornadoes have a different probability of rotating clockwise or anticlockwise. Our ongoing research programme on tornadoes in Mexico has shown that the number of tornadoes is significantly higher than previously thought. About 40% of all tornadoes occur in the complex topographic region of the Trans-Mexican Volcanic Belt. Data collected (from Internet videos) on the rotation of tornadoes formed in this region showed that about 50% of them rotated in a clockwise direction, contradicting tornado statistics for most of North America. Time series of the helicity parameter showed that tornadoes formed in topographically complex areas exhibited different behaviours compared to those formed in plains that are related with supercell systems.